Capital social em um arranjo produtivo local: estudo da indústria têxtil e de confecção do município de Americana e região - Teixeira, Ana Flávia (2010)
The process of economic globalization, intensified in the late twentieth century, has produced a strong impact on the productive structures, requiring of them a new position on how to organize themselves. Aiming to transpose its limitations and difficulties and, thus, become able to face the new demands of this context of intense competitiveness, many companies have tried to establish alliances among themselves. Among the main models of partnerships, it is highlighted the one of business networks. In Brazilian case, such associations have been occurred, mainly, by the spatial concentration of companies in the figure of Local Productive Arrangements. These structures, in their turn, refers to a set of organizations located in the same territory, which are articulated, developing joint actions aimed at reaching common goals. However, this atmosphere of cooperation is only possible with the construction of social capital. Thus, this paper proposes to discuss the importance of such resource in the formation of the LPAs. Therefore, it was promoted a qualitative study, opting for conducting a field survey along the Textiles and Apparel Productive Arrangement of the cities of Americana, Hortolandia, Nova Odessa, Santa Barbara D'Oeste and Sumaré. In total, nineteen companies participated in this process, responding to an instrument for collecting data and presenting, in a semistructured interview, their perspectives of the themes raised. Through the examination of the information obtained, it was shown that the volume of interactions among the companies participating in the LPA is still small, a consequence of the small commitment and engagement on the part of the business community. Also, configure, largely, weak ties, personal and recent (so-called "known"). Therefore, the network is not very dense and cohesive, presenting a environment disinclined to the flow of information with high reliability and refinement levels, and not favorable to building trust. Thus, we have that social capital is not very present in this arrangement, which results a low level of cooperation between companies. Much remains to be done for the effective formation of a Textile and Apparel LPA in Americana and region